PEMANFAATAN ZEOLIT ALAM SEBAGAI MEDIA PENDUKUNG AMOBILISASI ENZIM α-AMILASE - Septiani, Upita; Lisma, Agrina (Universitas Andalas, 2011)
ABSTRACT The utilization of natural zeolite as supporting media of α-amylase enzyme has been done. Natural zeolite which is activated with 3M HCl can remove impurities in the surface natural zeolite, uncover and widen the pores of the zeolite and activate functional groups to interact with α-amylase enzyme in the process of immobilization enzyme process. The mass of activated natural zeolite which is used as a material immobilized to get the optimal activity of α-amylase enzyme was 0.3 gram. Based on the measurement result of optimization of α-amylase enzyme were obtained optimum temperature of 35 oC, pH 5.6 and incubation time of 35 minutes with 0.04845 units/mL of the unit activity. And for α-amylase immobilized enzyme will be stable at the optimum temperature of 50 oC, pH 5.6 and incubation time of 45 minutes with 0.030 units/mL of the unit activity. SEM-EDX pattern shows the differences in surface morphology between natural zeolite and activated natural zeolites which contain α-amylase enzyme. A mobilization technique can increase the stability utilized in a α-amylase enzyme. Keywords : Zeolite, amobilization, α-amylase enzyme